2008
DOI: 10.1007/s11938-008-0002-1
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-induced bowel dysfunction

Abstract: Opioid-induced bowel dysfunction (OIBD) is a potentially debilitating side effect of chronic opioid use. It refers to a collection of primarily gastrointestinal motility disorders induced by opioids, of which opioid-induced constipation (OIC) is the most common. Management of OIBD is difficult, and affected patients will often limit their opioid intake at the expense of experiencing more pain, to reduce the negative impact of OIBD on their quality of life. Effective pharmacologic therapy for OIC is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, the results of a long-term safety study found that alvimopan was associated with an increased risk of cardiovascular events compared with placebo. These findings have been investigated to determine their clinical relevance and the potential consequences for the safety of alvimopan, especially for long-term use [84,85] . Alvimopan is registered in the USA for treatment of postoperative ileus, but is contraindicated in patients using opioids for more than 7 days.…”
Section: Other Potential Strategiesmentioning
confidence: 99%
“…However, the results of a long-term safety study found that alvimopan was associated with an increased risk of cardiovascular events compared with placebo. These findings have been investigated to determine their clinical relevance and the potential consequences for the safety of alvimopan, especially for long-term use [84,85] . Alvimopan is registered in the USA for treatment of postoperative ileus, but is contraindicated in patients using opioids for more than 7 days.…”
Section: Other Potential Strategiesmentioning
confidence: 99%
“…Gender ( p = 0.009), opioid use ( p = 0.034), BPI severity score ( p = 0.021), and BPI interference score ( p < 0.001) are significantly associated with OIC. Taking into account the available literature [ 28 , 40 , 41 ], we decided to include depressive disorders diagnosis in our multivariate regression analysis model.…”
Section: Resultsmentioning
confidence: 99%
“…Morphine seems to be the opioid with the highest associated risk of OIC, while transdermal preparations of Buprenorphine and Fentanyl are associated with lower risk [ 25 ]. However, the prevalence may also vary due to differences in clinical supervision on OIC development and prophylactic laxative therapy prescription, as well as variability in patient's perception of their constipation symptoms [ 19 , 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving opioid medication for postoperative or chronic pain often have opioid-induced bowel dysfunction (OBD). The most common symptoms of OBD are intestinal motility disorder and constipation ( 37 - 41 ). 4) Abdominal muscles contraction is one of the factors in defecation.…”
Section: Resultsmentioning
confidence: 99%